Analisis Sistem Pembagian Waris Dua Banding Satu dalam Perspektif Maqasid Syariah: Keadilan dan Kesejahteraan dalam Warisan Keluarga - Arif Fikri; Rudi Santoso1; Miswanto (CV. Creative Tugu Pena, 2024)
This research examines the 2 to 1 inheritance distribution system from a maqasid sharia perspective, with a focus on justice and prosperity in family inheritance. The distribution of inheritance in Islamic law, especially which stipulates that men have twice the rights compared to women, often triggers controversy regarding gender issues. Through a library research approach, this research analyzes how the principles of maqasid sharia—protection of the soul, mind, and offspring—can be integrated to formulate a fairer and more sustainable distribution system. Research finds that understanding inheritance law, social norms, economic conditions and education have a significant influence on the implementation of this system. In addition, challenges in upholding justice and adapting inheritance provisions to the modern context are also identified. Thus, this research provides recommendations for more inclusive inheritance law reform, ensuring that the principles of maqasid sharia are applied to achieve wider benefits, for the welfare of all family members, especially women.